Effect of vanadium on microstructure and wear behaviour of Fe based C–B–Ni hardfacing alloy. (August 2015) - Rovatti, L.; Casati, R.; Emami, A.; Lecis, N.; Stejskal, O.; Andrianopoli, C.; Vedani, M.
<x content-type="archive" xml:space="preserve">Abstract</x> To investigate the influence of chemical compositions of different hardfacing alloys on wear performance experimental high vanadium Fe–C–B–Ni alloys in the form of blended powders have been cast in a laboratory furnace and analysed in three configurations: hypereutectic, near-eutectic and hypoeutectic. The solidification behaviour was defined by differential scanning calorimetry while the main microstructural features were characterised by microscopy, X-ray diffraction and microhardness as well as pin-on-disc wear tests. Fe–V rich powders to an originally hypereutectic Fe–C–B–Ni alloy induced the shift to hypoeutectic solidification and promoted the presence of larger quantities of hard V-rich carbides. The new V-bearing alloys showed higher wear performance and higher bulk hardness than the reference alloy. The improved wear properties were mainly due to the precipitation of fine V-rich carbides that effectively reinforced the structure without any evidence of pull-out and cracking of the smaller particles.